THE MANAGEMENT OF CICATRICIAL ECTROPION CAUSED BY BURN INJURY: A CASE REPORT - Okiningtyas Kun Cahyandari; Doemilah, Ratna (Majalah Oftalmologi Indonesia, 2024)
Introduction: Eyelid reconstruction in cicatricial ectropion caused by facial burns represents a surgical challange. Surgical management consists in correcting the lid defect often associated with a skin graft and lid tightening. Case Description: a 18-years-old man was referred because suffered cicatricial ectropion on superior-inferior eyelid of right eye after got burn injury 4 months before come to our outclinic, with cicatricial tissue on 50% on right face after facial burns. Ocular examination revealed a visual acuity 20/20 on both eyes, lagophthalmos but a good Bell’s phenomenon, and diffused ectropion on the eyelid of right eye. Reconstruction was made a release contracture tissue, lid tightening and full thickness skin grafts from donor site which recommended from supraclavicular 60 x 30 mm for superior eyelid and 50 x 40 mm for inferior eyelid, place the graft and fix it with a bolster and Frozt suture. We follow up the patient, 1 day, 1 week, and 6 months post operation. Discussion: Major issues when addresing cicatricial ectropion followed by severe burns are : right donor site selection, slightly oversized graft allowed for some contraction and full eyelid closure. For further plan is consultation to plastic surgery to manage other cicatricial tissue of part of body.   Conclusion: Reconstruction for diffused ectropion by using full thickness skin graft and lid tightening are better option for correction of cicatricial ectropion.